Challenges and Novelties in the Treatment of Obesity in Adults. A review - Karolina Kuczapska; Marek Kurowski; Anna Gliwa; Monika Ryglewicz; Dariusz Fabian; Elżbieta Leszczyńska-Knaga; Natalia Jakubczyk; Weronika Rutkowska-Kawalec; Paweł Moczydłowski; Karolina Michalczuk (Journal of Education, Health and Sport)
Introduction